Effect of Work Facilities and the Apllication of Technology Utilization on the Performance Capabilities of Employees of PT Indomarco Prismatama In Sukabumi Regency Branch - Mulyani, Hesti (PT Naureen Digital Education, 2024)
The development of the digital era at this time can be characterized by developments in the facilities and technology used in a company. Increasingly, with the development of technology, workers cannot be separated from technology. Work facilities and technology develop in such a way as needed. This can make it easier for employees to simplify their work processes so that they can save time. Based on the results of preliminary research conducted on PT Indomarco Prismatama employees at the Sukabumi Regency branch, the results showed that the performance capabilities of PT Indomarco Primatama employees at the Sukabumi Regency branch were considered not optimal. This can be seen from the declining performance of some employees. Moreover, especially in carrying out work that has been determined by the leadership of the company. The ability of employees' performance can be increased if there is a match between the work performed and the ability. So thus that employees have good performance abilities must be able to understand the work given and be able to know how the procedure for doing the work given by the leadership is good and right. So that it can provide maximum performance results. This study aims to determine the effect of work facilities and the application of technology utilization on the performance capabilities of employees of PT Indomarco Primatama in the Sukabumi Regency branch. This study uses a quantitative approach method. The types of data used in this research are primary data and secondary data. Primary data collection method is done by using a questionnaire. The sample used in this study were 32 respondents consisting of PT Indomarco Primatama employees at the Sukabumi Regency branch. The analysis used is Multiple Linear Regression. The results of the analysis show that the regression equation formed is Y = 8,134 + 0,278 x1 + 0,132 x2 . The results of this study can be concluded that there is an influence between work facilities and the application of technology utilization on the performance abilities of employees of PT Indomarco Primatama in the Sukabumi Regency branch.